Revisiting Covered Interest Parity in the European Union: the DCCA Approach - Ferreira, Paulo (2016)
This paper analyzes the evidence of financial integration, with covered interest parity (CIP), for a group of countries that have already adopted the euro and another group of countries that kept their currencies. We use detrended crosscorrelation analysis, which allows analyzing the behavior of time series even when they are not stationary. The main results indicate that countries that adopted the euro do not show much evidence in favor of CIP, before joining the Eurozone, which could imply they will not benefit from all common currency advantages. In the group of countries that did not adopt the euro, Denmark, Sweden, the UK and the Czech Republic are the ones presenting better conditions for financial integration with the euro, while Bulgaria has also some evidence of this. Some possible explanations of CIP deviations are agents not considering all countries’ assets as similar and also the underdevelopment of markets and liquidity problems (more pronounced due to periods of turmoil).